2012
DOI: 10.5352/jls.2012.22.7.857
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Opuntia humifusa Supplementation on Lipid Peroxidation and SOD Protein Expression in the Liver, Kidney, and Skeletal Muscle of Rats Fed a High-fat Diet

Abstract: This study was conducted to investigate the effects of Opuntia humifusa supplementation on lipid peroxidation and superoxide dismutase (SOD) protein expression at resting state in various organs of rats fed a high-fat diet. Sixteen Sprague-Dawley male rats, 6 weeks of age, were randomly divided into two groups: a control diet group (CG, n=8) and an experimental diet group (EG, n=8). They were given a high-fat diet (CG) or a diet supplemented with 5% of O. humifusa (EG) for 8 weeks. The results showed that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…reported that the vitamin C content in an OH stem is approximately 260.94 mg/100 g, which is higher than that in Opuntia ficus-indica [12]. Kwon et al (2012) and Kang et al (2013) found abundant minerals, such as calcium (Ca), magnesium (Mg), iron (Fe), sodium (Na), and potassium (K), in OH stems and fruits [13,14]. The abundance of natural antioxidants in these plants, primarily in their phenolic and flavonoid compounds, is believed to contribute significantly to their antioxidant capacity.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…reported that the vitamin C content in an OH stem is approximately 260.94 mg/100 g, which is higher than that in Opuntia ficus-indica [12]. Kwon et al (2012) and Kang et al (2013) found abundant minerals, such as calcium (Ca), magnesium (Mg), iron (Fe), sodium (Na), and potassium (K), in OH stems and fruits [13,14]. The abundance of natural antioxidants in these plants, primarily in their phenolic and flavonoid compounds, is believed to contribute significantly to their antioxidant capacity.…”
Section: Introductionmentioning
confidence: 90%
“…The main characteristics of the 15 studies are summarized in Table 1. Among the fifteen articles, four studies reported a positive association between the optical application of OH and reductions in skin aging [5,[19][20][21], nine studies found anti-cancer benefits [6,7,15,[21][22][23][24][25][26], and three studies demonstrated the beneficial effects of OH in reducing symptoms of diabetes [9,11,13,14,27]. OH species are cultivated primarily in Korea; thus, all of these studies were performed only in Korea, covering the period from 2005 to 2020.…”
Section: Description Of Included Studiesmentioning
confidence: 99%